PENDIDIKAN AGAMA ISLAM DALAM PERSPEKTIF FILSAFAT: ANTARA CITA DAN FAKTA - Mohamad Arif Majid (IAIN Kediri, 2015)
Islamic education is a long life process in digging and performing Islamic values of (raá¸¥matan li al-â€™alamÄ«n).Â It is also long-life attempts to excavate raá¸¥matan values amid the challenges of modernity and thoughts. ThisÂ article discusses Islamic education from a philosophical perspective. This study found that ontologically theessence of Islamic education is on the process, while epestemoligically it requires the interaction between ratioÂ and revelation. Axiologically, Islamic education should bring dignity, prominence, and happiness both in theÂ word and the hereafter. This is what the so-called a â€˜two in oneâ€™ concept and the key is â€˜lillÄh.Keywords: Pendidikan Agama Islam, Filsafat, Raá¸¥matan li al-â€™AlamÄ«n